The House Guest - Northedge, Charlotte (London : HarperCollinsPublishers, 2021)
When Kate moves to London after the disappearance of her sister, she's in need of a friend. A chance meeting leads Kate to Della, a life coach. Della takes a special interest in Kate, and Kate soon finds herself entangled in Della's life. It's only when she realises that she's in too deep that Della's veneer begins to crumble
Keywords: Female friendship -- Fiction; Personal coaching -- Fiction; Missing persons -- Fiction; London (England) -- Fiction; Thrillers (Fiction); Psychological fiction